Analisis Curah Hujan Ekstrem El-Nino dan Dampaknya terhadap Neraca Air Tanah dan Penentuan Waktu Tanam pada Dua Wilayah dengan Pola Hujan Lokal dan Ekuatorial di Provinsi Maluku - Panggua, Merson; Kunu, Pieter J; Riry, Johan (MAKILA, 2025)
El Nino is one of the global phenomena that has affected the climate system of Indonesia. One of the direct impacts of the El Nino phenomenon is the decrease of water availability on agricultural land. This study aimed to analyze the period of El-Nino extreme rainfall events and to analyze the impact of El Nino extreme rainfall events on the availability of ground water for plant growth and determining planting times in areas with local rainfall patterns and equatorial rainfall patterns. This study uses several elements of Meteorological weather parameters, namely, temperature, wind speed, air humidity, sunlight and rainfall over a period of 30 years (1994-2023). The approach used is descriptive-analytical, emphasizing the analysis of average rainfall data, analysis of extreme El Nino rainfall, analysis of land water balance and analysis of planting seasons. Based on the results of the analysis and discussion, it was found that El Nino extreme rainfall has a significant influence on areas with local rainfall patterns and equatorial rainfall patterns. The role of the government is needed by providing counseling and socialization to prepare farmers to adapt to climate change.Further research is needed to examine the planting season adaptation strategy based on the type of plant that is appropriate to the extreme water deficit conditions due to El-Nino